The Cuban Model for Higher Education of Older Adults: Generativity, Social Commitment, and Collaborative Work - Yuni, Jose Alberto (2014)
The present work is an approach to study the Cuban model for educating the elderly, and its aim is to describe the main features of the experience developed by this country. The University of the Third Age is more than three decades old in Latin America, but none of the countries in the region can show a state educational policy regulating and orienting its development. Cuba is the only country that has designed an educational program for older adults at a national level. The model is the most outstanding one among the rest of the countries in the American continent. This research is based on documentary analysis and interviews held with leaders and managers of the Chair for Older Adults, who were located in different towns of Cuba. Results led to a reconstruction of a set of dimensions of the Cuban model, such as the process of institutionalization, syllabus organization, the process of expansion and universalization, and educators' training strategies for elders. Finally, bearing in mind the features of Cuban political organization and gerontological positions, it was possible to draw the future evolution and challenges faced by the Cuban model for educating older adults.